THE READINESS OF FOREIGN WORKERS REGULATIONS IN THE ENGINEERING AND MEDICAL PRACTITIONERS SECTOR ENTERING THE ASEAN ECONOMIC COMMUNITY - Agusmidah, Agusmidah; Siregar, Mahmul; Putra, Mohammad Eka (Faculty of Law, Universitas Jenderal Soedirman, 2016)
Protection of the domestic labor market and prevention of skilled foreign workers entry through negative list are not in accordance with free market principle of the ASEAN Economic Community (AEC) to be implemented in ASEAN countries such as Indonesia in the second half of 2015. However, restrictions are still practiced by some Indonesian government institutions, such as Ministry of Health for doctors, dentists, and nurses, the Ministry of Public Works for surveyors, and the Ministry of Tourism for tourism profesionals. Through literature study and legal analysis, it was found that foreign workers restriction by professional associations according to certain competency standards aims to prevent domestic work from being monopolized by skilled foreign workers in the AEC 2015 era.Keywords: ASEAN Economic Community (AEC), Indonesian regulation, skilled foreign workers